Cognició, temporalitat i lingüística comparada: el pretèrit perfet perifràstic i la metàfora del temps en català - Martos, Josep Lluís (Caplletra. Revista Internacional de Filologia, 1996)
Metaphor is a means of conceptualizing the world around us and an anthropological universal of expression wich helps us apprehend time in terms of space. The purpose of this paper is thus to analyse a series of time metaphors in Catalan, and more particularly the vado + infinitive construction, by showing the relationship between the conceptualizing system of Catalan and that Of other languages, such as English, German, Italian, Portuguese, French, and, especially, Occitan and Spanish.